CD14 Directs Adventitial Macrophage Precursor Recruitment: Role in Early Abdominal Aortic Aneurysm Formation. Issue 2 (8th March 2013) - Blomkalns, Andra L.; Gavrila, Daniel; Thomas, Manesh; Neltner, Bonnie S.; Blanco, Victor M.; Benjamin, Stephanie B.; McCormick, Michael L.; Stoll, Lynn L.; Denning, Gerene M.; Collins, Sean P.; Qin, Zhenyu; Daugherty, Alan; et al.
Abstract : Background: Recruitment of macrophage precursors to the adventitia plays a key role in the pathogenesis of abdominal aortic aneurysms (AAAs), but molecular mechanisms remain undefined. The innate immune signaling molecule CD14 was reported to be upregulated in adventitial macrophages in a murine model of AAA and in monocytes cocultured with aortic adventitial fibroblasts (AoAf) in vitro, concurrent with increased interleukin‐6 (IL‐6) expression. We hypothesized that CD14 plays a crucial role in adventitial macrophage precursor recruitment early during AAA formation. Methods and Results: CD14 −/− mice were resistant to AAA formation induced by 2 different AAA induction models: aortic elastase infusion and systemic angiotensin II (AngII) infusion. CD14 gene deletion led to reduced aortic macrophage infiltration and diminished elastin degradation. Adventitial monocyte binding to AngII‐infused aorta in vitro was dependent on CD14, and incubation of human acute monocytic leukemia cell line‐1 (THP‐1) monocytes with IL‐6 or conditioned medium from perivascular adipose tissue (PVAT) upregulated CD14 expression. Conditioned medium from AoAf and PVAT induced CD14‐dependent monocyte chemotaxis, which was potentiated by IL‐6. CD14 expression in aorta and plasma CD14 levels were increased in AAA patients compared with controls. Conclusions: These findings link CD14 innate immune signaling via a novel IL‐6 amplification loop to adventitial macrophage precursor recruitment in the pathogenesis of AAA.